Measurement of in-medium jet modification using direct photon + jet and π0 + jet correlations in p + p and central Au + Au collisions at √sNN = 200 GeV - Aboona, Bassam; Deppner, Ingo Martin; Herrmann, Norbert; Leung, Yue; Söhngen, Yannick; Weidenkaff, Philipp (Physical review letters, 2025)
The STAR Collaboration presents measurements of the semi-inclusive distribution of charged-particle jets recoiling from energetic direct-photon (𝛾dir) and neutral-pion (𝜋0) triggers in 𝑝 +𝑝 and central Au +Au collisions at √𝑠𝑁⁢𝑁 =200 GeV over a broad kinematic range, for jet resolution parameters 𝑅 =0.2 and 0.5. Medium-induced jet yield suppression is observed to be larger for 𝑅 =0.2 than for 0.5, reflecting the angular range of jet energy redistribution due to quenching. The predictions of model calculations incorporating jet quenching are not fully consistent with the observations. These results provide new insight into the physical origins of jet quenching.